Legal Aspects of Marketing and Sales - Mayer, Don; Warner, Daniel; Siedel, George J.; Lieberman, Jethro K. (Open textbook library., 2012)
Legal Aspects of Marketing and Sales is an up-to-date textbook that covers legal issues that students who will work in marketing or with marketing managers must understand. The text is organized to permit instructors to tailor the materials to their particular approach. The authors take special care to engage students by relating law to everyday events with their clear, concise and readable style. After introductory chapters covering the legal environment of business, Legal Aspects of Marketing and Sales provides students with context and essential legal concepts relating to contracts, sales, intellectual property, antitrust law and unfair trade practices. The text provides the vocabulary and legal savvy they will need to talk in an educated way to customers, suppliers, shareholders, government regulators and other stakeholders — and to their own lawyers.